EFEKTIVITAS INTERNALISASI BUDAYA DAN NILAI PERUSAHAAN MELALUI PROGRAM ONBOARDING 'EMTRACKS' PADA KARYAWAN BARU PT. ELANG MAHKOTA TEKNOLOGI TBK (EMTEK) GROUP - Maharani, Gusti Ayu Made Devyna; Iryanti, Endang (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The implementation of employee onboarding at the PT Elang Mahkota Teknologi Tbk. (EMTEK) group was presented in an innovative way over time, until the method of onboarding was created under the name 'EMTRACKS'. This program aims to introduce the EMTEK group, starting from the incorporated companies, corporate values and culture, to group games as an implementation of corporate values and culture to new employees. However, the effectiveness of internalizing corporate culture and values through EMTRACKS needs to be analyzed to identify areas that need to be improved, in order for the onboarding program to optimally convey values and culture to new employees. The purpose of this study is to determine the extent to which the effectiveness of the implementation of onboarding to new employees of EMTEK in internalizing the Company's culture and values. This is reviewed from several aspects, ranging from duration, material, to delivery methods. The research approach used is a qualitative method through participatory observation along with participant interview after onboarding is completed. This survey is designed to capture the impression of the 'EMTRACKS' onboarding program that they have participated in. The results of this study show that the EMTRACKS program proved effective in conveying EMTEK Group's values and work culture to new employees through interactive and creative approaches. However, development of activity design and communication needs to be improved to ensure maximum participation and optimum internalization of culture and values to new employees. Overall, EMTRACKS is an effective and innovative onboarding model in building new employees' engagement with the company culture